Interface Amorphization of Two-Dimensional Black Phosphorus upon Treatment with Diazonium Salts - Mitrovic, Aleksandra; Wild, Stefan; Lloret, Vicent; Fickert, Michael; Assebban, M'hamed; Markus, Bence G.; Simon, Ferenc; Hauke, Frank; Abellán, Gonzalo; Hirsch, Andreas (Chemistry - A European Journal, 2021)
Two-dimensional (2D) black phosphorus (BP) represents one of the most appealing 2D materials due to its electronic, optical, and chemical properties. Many strategies have been pursued to face its environmental instability, covalent functionalization being one of the most promising. However, the extremely low functionalization degrees and the limitations in proving the nature of the covalent functionalization still represent challenges in many of these sheet architectures reported to date. Here we shine light on the structural evolution of 2D-BP upon the addition of electrophilic diazonium salts. We demonstrated the absence of covalent functionalization in both the neutral and the reductive routes, observing in the latter case an unexpected interface conversion of BP to red phosphorus (RP), as characterized by Raman, P-31-MAS NMR, and X-ray photoelectron spectroscopies (XPS). Furthermore, thermogravimetric analysis coupled to gas chromatography and mass spectrometry (TG-GC-MS), as well as electron paramagnetic resonance (EPR) gave insights into the potential underlying radical mechanism, suggesting a Sandmeyer-like reaction.
CRIS-Team WoS Importer:2021-02-19